A work study on Need's Footwear Factory - Deriada, Gerald John (College of Engineering, 2000)
A methods engineering study was conducted on Need's Footwear Factory from January to March 2000. This study was timely since the manager of the factory was interested in investigating how the existing production system could be improved. For this study, shoe type SM01 was chosen. The first part of the study dwelt on system documentation. Operational and personnel relationship charts were made. Standard time was determined through the snap back method using appropriate forms. The second part consisted of problem identification, verification and analysis. The study proponents applied the Kepner-Tregoe Approach and constructed a Streamline Diagnostic Diagram, an Ishikawa Diagram, and a Root Cause Verification Matrix. The last part focused on the generation and evaluation of alternatives. Risks and possible future problems were also assessed and contingency measures were developed. The current standard time for manufacturing 40 pairs of SM01 shoes is 18.59 hours. To improve the standard time, in particular, and to improve the work conditions in the factory, in general, the following alternatives should be implemented : briefing the workers on fire prevention, enforcing the "No Smoking" policy, prohibiting the workers from gossiping, prohibiting eating near the storage area, increasing manager-worker interactions, requiring the workers to wear masks always, mounting the lamps properly, positioning the fire extinguishers strategically, disposing of unusable raw materials, replacing mismatched chairs and tables, providing additional trashcans, tearing a wooden partition, transferring the sewing machine, and introducing new forms. The suggested period of implementation is between March and April, when the production volume is low. The total expected expenses in implementing the fifteen recommendations is estimated to amount to PhP3,200.00. Since the management of Need's Factory is considering an expansion of its shoe-manufacturing business, the work study just completed might prove to be helpful.